A novel fast distance relay for series compensated transmission lines. (January 2015) - Qi, Xuanwei; Wen, Minghao; Yin, Xianggen; Zhang, Zhe; Tang, Jinrui; Cai, Fei
Highlights: We propose a novel fast distance relay for series compensated transmission line. We use the theory of equal transfer process of transmission lines. The fault zone can be identified effectively and simply. This method can achieve fast operating speed and high accuracy. The transient error of the measuring distance is reduced to a great extent. Abstract: This paper presents a fast distance relay for series compensated transmission lines based on the R–L differential-equation algorithm using the theory of equal transfer process of transmission lines. The measuring distances based on the proposed algorithm can fast approach the actual value of fault distance when a fault occurs in front of the series capacitor. When a fault occurs behind of the series capacitor, the fault loop, including the series capacitor, does not match the R–L transmission line model, so the measuring distances fluctuate severely. Based on this, the relative position of the fault with respect to the series capacitor can be judged effectively according to the fluctuation range of the measuring distances, and the accurate fault location can be obtained fast. A variety of PSCAD/EMTDC simulation tests show that the new relay has fast operating speed and high accuracy when applied to the long series compensated transmission lines.